The Influence of Actual Appraisals of Peers on the Self-Appraisals of Personality Traits for Chinese Late Adolescents: The Mediating Effect of Reflected Appraisals - Yue, Caizhen; Long, Yihong; Yang, Zhiwen; Xiao, Qianguo; Pan, Weigang (Frontiers in Psychology, 2021)
Reflected appraisals refer to individuals’ perceptions of how they are perceived by others. Numerous studies in culture psychology have revealed that individuals in the Eastern collectivist culture show an interdependent self-construal, which depends much on the social culture. Hence, the research on reflected appraisals in the Eastern culture can improve the understanding of how the social environment shapes the individual’s self-perception. In this study, we aim to explore the relationships among self-appraisals, reflected appraisals and peers’ actual appraisals of the Big Five Personality for Chinese late adolescents. Participants were divided into sixteen groups, with two to four people of each group who were familiar with each other. Each participant was told to fill out the questionnaires of reflected appraisals, peers’ actual appraisals and self-appraisals. Through analyzing 164 sets of data, the results show that: a) The scores of reflected appraisals are significantly lower than that of peers’ actual appraisals. b) The relationships among the reflected appraisals, peers’ actual appraisals and self-appraisals are distinct on different personalities. For extroversion, there are significant mediums to high degree relationships among the three types of appraisals; while for the agreeableness, conscientiousness, emotional stability and openness, self-appraisals are highly correlated with reflected appraisals, reflected appraisals show low degree correlation with peers’ actual appraisals. c) Reflected appraisals play a mediating role between peers’ actual appraisals and self-appraisals. Our study suggests that individuals in Chinese culture generally underestimate how the peers perceive them. Furthernore, peers’ actual appraisals affect individuals’ self-concepts through reflected appraisals. This study revealed the unique personality feature of self-modesty under the background of Chinese culture and the importance of peers on the development of self-concepts for Chinese late adolescents. This study can shed new light on the understanding of the development of self-concepts for late adolescents under different culture backgrounds.